2017
DOI: 10.1177/1052562917710686
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Moral Conviction Theory of Student Cheating: An Empirical Test

Abstract: In this article, we develop an integrated moral conviction theory of student cheating by integrating moral conviction with (a) the dual-process model of Hunt–Vitell’s theory that gives primacy to individual ethical philosophies when moral judgments are made and (b) the social cognitive conceptualization that gives primacy to moral identity. We found empirical support for our proposed model in a study with 311 business students where moral conviction predicted student moral disengagement and subsequent unethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 107 publications
(160 reference statements)
1
5
0
Order By: Relevance
“…H4: As depicted in Figure 1 , and consistent with previous research (Hunt and Vitell, 2006 ; Detert et al, 2008 ; Roberts et al, 2017 ), moral judgment was expected to have both direct and indirect associations with academic dishonesty. Specifically, moral judgment was hypothesized to have a direct negative relationship with academic dishonesty as well as indirect associations through both responsibility judgment and moral disengagement.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…H4: As depicted in Figure 1 , and consistent with previous research (Hunt and Vitell, 2006 ; Detert et al, 2008 ; Roberts et al, 2017 ), moral judgment was expected to have both direct and indirect associations with academic dishonesty. Specifically, moral judgment was hypothesized to have a direct negative relationship with academic dishonesty as well as indirect associations through both responsibility judgment and moral disengagement.…”
Section: Introductionsupporting
confidence: 81%
“…Toward this end, numerous theories of ethical decision-making and moral functioning have been proffered (e.g., Sykes and Matza, 1957 ; Festinger, 1962 ; Fishbein and Ajzen, 1972 ; Blasi, 1980 , 1983 , 1984 ; Kohlberg and Candee, 1984 ; Bandura, 1986 ; Rest, 1986 ; Beck and Ajzen, 1991 ; Weiner, 1995 ; Rest et al, 1999 ; Bergman, 2002 ; Roberts et al, 2017 ). Albeit operationalized with different constructs, motivation and self-regulation are central to all theories in explaining or bridging the gap between moral cognition and action.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion encourages universities to make efforts to improve students' moral honesty. The study Roberts, Thomas, Novicevic, Ammeter, Garner, Johnson, & Popoola (2018) found that moral beliefs predict students' moral disengagement and subsequent unethical decision making related to academic dishonesty not only directly but also indirectly through the philosophy of ethics and moral identity of students. By being honest, learning outcomes can be better.…”
Section: Discussionmentioning
confidence: 92%
“…Researchers in psychology distinguish between clinical narcissism (a personality disorder) and trait narcissism. Trait narcissism is viewed as a relatively stable personality characteristic that is normally distributed in the adult population [38], [39]. In interpersonal contexts, trait narcissism serves as both a personality trait and as a self-regulatory mechanism, wherein the narcissist's motivations, relationships with others, and self-regulatory strategies interact to drive behavior [39].…”
Section: Students' Moral Development Affects Students' Academic Fraud Behaviormentioning
confidence: 99%